Effect of corn substitution as energy source in palm kernel cake and urea treated rice straw- based diet in dorper crossbred lambs - Saeed, Osama Anwer (2018)
Modern ruminant production has become increasingly affected by current economic trends. In recent years, dramatic increases in the price of feedstuffs caused by competition for human consumption. Feed accounts for 50% to 75% of total production costs in the livestock industry, making it one of the largest expenses for producers. As the land available for agricultural production is decreasing, and the price of feed inputs increasing, it has become more important for producers to understand the potential value of utilizing byproducts as part of a feeding program. This study investigated corn substitution and its effect on PKC and urea-treated rice straw-based diet on the rumen fermentation, biohydrogenation and growth performance of Dorper crossbred lambs. Apart from that, hematological and biochemical profile of blood serum; carcass characteristics and quality of meat were also examined in this study. Two experiments involving in vitro rumen fermentation and in vivo feeding trials were conducted. For the in vitro rumen fermentation analysis, three treatment groups with different level of corn were used; namely T1 = basal diet (control); T2 = basal diet + 5% corn and T3 = basal diet +10% corn. In this study, corn was used as a source of energy. The T1, T2 and T3 were incubated from 0 h until 72 h to determine the fermentation profiles, fatty acid biohydrogenation and also rumen microbial population. The second experiment involved 27 Dorper crossbred lambs (initial b/w 15 + 0.59 Kg) that individually kept in single pens and were randomly divided into 3 formulated dietary group consisting of T1 = 75.3% PKC + 0% corn; T2 = 70.3% PKC + 5% corn and T3 = 65.3% PKC + 10% corn. Feed intake and refusal were recorded on a daily basis. Blood samples for hematological and biochemical tests were collected from all the lambs at days 0, 40, 80, 120 of the experiment periods. The results of the in vitro study demonstrated that production of gas increased from 0 h until 9 h with T2 having the highest gas production during this phase. After 48 h, the gas production began to decrease gradually with increase in incubation time. No significant differences (P>0.05) were observed in the in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), NH3-N, and pH at 72 h. However, significant production of methane gas levels was noted in T3 which showed the highest CH4 concentration in comparison with the control group (T1) and T2. The population of microbials revealed that number of total methanogenic archaea increased at 24 h with T1 having the highest number followed by T3 and T2. However, no significant differences were observed between treatment groups for total bacteria, F. succinogenes and R. flavefaciens. The mean concentration of protozoa at 24 h revelated that T2 had the highest number of protozoa than others (P<0.001). Results of the in vivo feeding study demonstrated that diets substituted with corn were nearly similar in DM, CP, EE, and ash contents. Significant different were observed on the final body weight among the different treatment diets. Furthermore, significant different were observed for ADG in T3 than the other two treatments while the average daily feed intake was significant (P<0.05) for lambs fed on diet substituted 10% corn and 65.3% PKC was higher than the control lambs. It was found that lambs fed on diet substituted with 5% and 10% corn had highest (P<0.05) DMI than those substituted 0% corn. Moreover, biological values and protein efficiency ratios were significantly raised in lambs fed on diet contain 10% corn than those contain with 0% and 5% corn. However, significant differences in the number of protozoa demonstrated with T3 followed by T2 and T1 (P<0.05) but no differences of total bacteria, F. succinogenes, R. albus and methanogenic archaea. The number of R. flavefaciens was highest in T2 and T3 compared with T1. Substitution 5% and 10% corn as source of energy on the hematological and biochemical parameters in lambs has no effect on the serum appeared to be within a normal range. The serum antioxidant enzyme (GPx) demonstrates a reduction of GPx in T3 at day 120, but not in T2 where the GPx concentration in serum increased. The MDA was not affected by supplements within the same period. Feeding PKC significantly increased Cu retention by 2.06, 4.19, and 4.14 mg/d respectively in the body. Zinc concentration in the serum, liver, and kidney also increased slightly when corn is added as an energy source in the diet. Serum Cu, Se, Fe, and Zn did not differ (P>0.05) between treatment groups, but Se and Fe were higher (P<0.05) at day 120, especially in T3 compared to T1. The concentration of serum Zn was lower (2.27 ppm) in T2 and T3 within the same period. The real-time PCR analyses revealed significant (P<0.01) up-regulation of ATP7A and MT-Ia genes in T3 while, hepatic Cu/Zn SOD and GPx4 mRNA were high expression in lamb hepatocytes in T3 compared with T1. The smallest hot carcass weight (10.15 kg) was seen in lambs fed on the control diet, whereas lambs fed diet has 10% corn has the highest hot carcass weight (11.46 kg). Hot and cold dressing percentages on slaughter weight of lambs fed on 5% and 10% corn shows no significantly (P>0.05) different with the control group. The highest pH value of supraspinatus and longissimus lumborum muscles were influenced by supplement treatment T2 and T3 (5.76, 6.11, and 5.76) and (5.63, 6.15, and 5.85) respectively. Further, the L* value (lightness index) of the same muscle differed (P<0.001) among all three treatments and the a* (redness index) and b* (yellowness index) values were not significant in the treatment groups. Dietary substitution of corn into the PKC-based diet can be used to enhance the useful fatty acids in muscles and offal without having to compromise the rumen microbial metabolism, growth performance, serum biochemistry, carcass traits, and meat quality in lambs.